EFFECTS OF PRE-CHILLING AND STRATIFICATION PERIODS ON SEED GERMINATION AND SEEDLING GROWTH OF PISTACIA KHINJOK STOKS - Jyad. A. AL Ashoo; Khalil. I. Aljomaely (Mesopotamia Journal of Agriculture)
This study was conducted in the forestry department nursery of Mosul University; to investigate the effects of stratification degrees & chilling on seed germination and seedlings growth of Pistacia khinjuk stock. The results revealed the superiority of seed stratification in 12°c stratification in comparison with 4°c stratification. the 12°c gave the higher averages of germination energy (%) , germination percentage (%) , Survival percentage (%) , Seedling length (cm.) & seedling diameter (mm), the averages were 26.96%, 36.39 % , 34.74% , 54.54 cm, 5.90mm respectively , Also the stratificated seeds for 20 days were superior in all characters and gave the highest average in germination energy 34.42% , germination percentage 49.80% survival percentage 46.36%, seedling length 55.41 cm., and seedling diameter 6.1 mm. The chilling period 48 hour was superior in characters of germination energy (29.95%) , germination percentage (40.33%) , Survival percentage (38.16%) , Seedling length (64.09)cm. and seedling diameter (6.37)mm.